Estudo de viabilidade para implantação de geração fotovoltaica em shopping centers na região de Curitiba - Silvestri, Alessandro Frederico (2014)
This paper presents the feasibility study to the implantation of photovoltaic generation in shopping centers. The text explains, firstly, the Brazilian energetic situation and the peculiarities of the electrical national system. Basic concepts about electricity generation, with a bigger emphasis on photovoltaic solar energy, are discussed. The operation and the components of the photovoltaic solar panels are explicated. The main technologies on the market and its characteristics are also mentioned. The standards and the regulation related to the photovoltaic solar panels installation to the utility grid are quoted as well. After the theoretical analysis, it’s made the study of the place where the panels will be installed, considering the electrical characteristics of the consumer, such as electric energy consumption at peak demand and off-peak hours. When the installations preliminary project is done, the impact that the photovoltaic solar panels will cause in the electric bill of the consumer will be analyzed, concluding the study after verifying the feasibility of the project.